Gestão democrática na perspectiva de Paulo Freire: narrativas autobiográficas - Silva, Edimicio Flaudisio (2022)
The democratic school faces difficult times today. There is little room for decision-making about curricular policy within the school itself and control actions, such as decisions about the content to be taught, external tests for students and the mandatory use of school materials, have been gaining more strength. This thesis aims to develop a critical self-reflection of my practice as a director, in order to identify possibilities and limits of democratic management in a public elementary school in a context of control ideology. The theoretical framework is based on the conceptions of Paulo Freire (1987,1996, 2013, 2018) and authors aligned with him: Ana Maria Saul (2012, 2016) Ana Maria Saul and Luís Armando Gandin (2017), Vitor Henrique Paro (1997, 2011, 2015) and Licínio C. Lima (012, 2013), who deal with the issue of democratic management in a critical-emancipatory perspective. The methodological procedures used in this investigation include the self-reflection of narratives elaborated from my experience, described in emblematic scenes that take place at important moments in the life of the school: planning and development of the curriculum, teacher training, pedagogical meetings, parents' meetings and student assessment. The description of the scenes is supported by the participant observation of situations experienced at school and the recording of experience reports of the director-researcher's actions, in each of these moments. The narratives will have, as a sieve of analysis, a conceptual Freirean plot, in which the following concepts are found: democratic management, participation, dialogue, autonomy and humanization. In the results, indications will be presented for the construction of a democratic management in the school, in times of ideology of control, seeking to demonstrate the existing conflicts and the possibilities of resistance